Food safety indicators of yogurt with vegetable supplements - Farida Smolnikova, Maksim Rebezov, Mars Khayrullin, Irina Dolmatova, Tatiana Zaitseva, Azat Nigmatjanov, Svetlana Kanareikina, Vladimir Kanareikin (International Journal of Modern Agriculture, 2021)
This paper studies the food safety indicators of yoghurt comprising additionally Vitamin C and vegetable supplements (pumpkin pureeand oat flour). The technological process of yogurt production includes milk fermentation with Thermophilik Yoghurt Culture YC–X 16 ferment. Storing for 7 days does not significantly change pH and density of yoghurt. Toxic elements, mycotoxins, antibiotics and pesticides are not detected. The mineral composition shows that developed yoghurt enriched with potassium, sodium, magnesium and calcium comparing with control yoghurt sample. Thus, developing yoghurt with combination of vitamin C and vegetable components satisfies the requirements of food safety.